Smart city indexes, criteria, indicators and rankings: An in‐depth investigation and analysis. Issue 3 (13th July 2022) - Toh, Chai Keong
Abstract: There are many indexes and ranking bodies on Smart Cities. However, most of these rankings have their own specific evaluation criteria and ranking methodologies. Currently, there are no uniformly and universally accepted methods for comprehensive and fair evaluation of smart cities. This is a problem as no ranking is widely accepted and universally agreed upon. This not only creates chaos but also confusion as to what indexes to follow. In this paper, 6 current smart city indexes (IMD‐SUTD Smart City Index, AT Kearney Global Cities Index, IESE Cities in Motion Index, EasyPark Cities of the Future Index, Mori‐Foundation Global Power City Index and Smart EcoCity Index) produced by major organisations are examined, discussed, and compared. Commonalities and differences are highlighted, revealing insights into the accuracy, comprehensiveness, shortcomings, acceptance and usage of these indexes and rankings. Finally, new evaluation factors are suggested and the rationale behind them are provided, in addition to the essential 8 criteria of economy, governance, technology, health, transport, environment, living and sustainability.